Kepastian Hukum Pada Regulasi Praktik Kedokteran Melalui Telemedisin untuk Optimalisisasi Prosedur Penegakan Diagnosis - Adib Gunawan; Nandang Sambas; Suminar, Sri Ratna (JOM, 2024)
This study examines legal certainty in the regulation of medical practice through telemedicine to optimize diagnostic procedures in Indonesia. Telemedicine enables remote healthcare services through information and communication technology, which is very beneficial in remote areas with limited access to healthcare facilities. Although telemedicine offers ease of access and lower costs, there are challenges in ensuring accurate diagnosis without direct physical examination. Health law in Indonesia needs to balance aspects of legal certainty, justice, and utility in telemedicine regulation. Various countries such as Malaysia and India have adopted specific regulations for telemedicine, which can serve as references for Indonesia. The diagnostic procedure through telemedicine must still adhere to conventional stages such as anamnesis and physical examination to ensure accuracy. Detailed and specific legal arrangements for application-based telemedicine are needed to maintain the professionalism and ethics of doctors in diagnosis. This study highlights the importance of effective communication between doctors and patients in telemedicine to avoid misunderstandings and misdiagnosis. The development of telemedicine regulations in Indonesia must consider evolving technology and the public's need for equitable access to healthcare services. Further research is needed to determine the best media used in telemedicine to provide input to the government in forming regulations.